Application of Criminal Procedures to Perpetrators of Corruption Crimes Based on Perma No. 1 of 2020 concerning Sentencing Guidelines Article 2 Article 3 of the Corruption Eradication Law - Najemi, Andi; Monita, Yulia; Erwin, Erwin; Sidiq, Muhamad (Faculty of Social and Political Sciences University of Bangka Belitung, 2023)
The Jambi Corruption Crime Court (Tipikor) in handing down crimes is more dominant in applying Article 3 compared to Article 2 against perpetrators who cause harm to state finances and handing down decisions in the light category, namely an average of 1 year and 11 months. Regarding this issue, the aim of the research is to carry out an analysis of the judge's decision in relation to the implementation of Perma No. 1 of 2020 concerning Sentencing Guidelines for Article 2 and Article 3 of the Corruption Law. By conducting a study of the Jambi Corruption Court's decision, the judge's decision will be evaluated in the light, medium and heavy categories, so that a clear picture of the judge's rationale in implementing PERMA No.1 of 2020 is obtained. The type of research is normative juridical, namely examining materials law, both primary, secondary and tertiary legal materials. The approach is to use a statutory approach and a case approach by analyzing cases related to the legal issues discussed. From the results of the research on the Jambi District Court's decision 1) The decision handed down by the Judge regarding the implementation of PERMA Number 1 of 2020 has not been used as a guideline in handing down the decision. This can be assessed from the verdict handed down by the judge. The length of the prison sentence imposed is not in accordance with the categories as formulated, namely the categories of state losses are the most severe, heavy, medium, light and lightest, where in each category there is a classification, namely the range of prison sentences imposed is adjusted to that category. 2) The aim of punishment in corruption cases is to recover state losses, but in the imposition of a substitute sentence imposed by the judge the aim of the sentence has not been realized, because in PERMA there is no regulation regarding guidelines for imposing additional punishment as replacement money.